ANALISIS PERSEDIAAN MATERIAL DENGAN METODE MATERIAL REQUIREMENT PLANNING PADA PEKERJAAN STRUKTUR PROYEK RSUD SIDOARJO - Alifia; Witjaksana, Budi (UKI Press, 2024)
In the world of construction, materials play an important role in the running of a project. Material is one of the main raw materials that greatly affects the amount of project costs. Material inventory affects the progress of work and planned costs. The problem of shortage and excess stock of materials is related to material inventory management. Therefore, material inventory planning is something that must be considered. This study aims to analyze and calculate the total cost of material inventory efficiently and minimally in the Construction of the Integrated Central Building of RSUD Sidoarjo Regency. The material inventory method used is Material Requirement Planning (MRP) with three approach techniques, namely Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The results of this study obtained lot sizing techniques with efficient MRP methods and minimum total material inventory using the Period Order Quantity (POQ) technique except for D10 Iron and D19 Iron using Lot For Lot (LFL) techniques. The costs incurred in the material inventory of each type of 4th-floor structure material are Multiplex Material t = 9 mm melamine Rp. 133,601,679, Iron Concrete D10 Rp. 212,685,500, Iron concrete D13 Rp. 171,485,930, Iron concrete D16 Rp. 56,760,803, Iron concrete D22 Rp. 155,031,888, and Concrete ready mix fc '= 25 Mpa Rp. 292,512,673. By using the right lot-sizing technique, it is expected to solve the problem of lack or excess material